Extending the body to virtual tools using a robotic surgical interface: evidence from the crossmodal congruency task. - Ali Sengül (Public Library of Science (PLoS), 2012)
The effects of real-world tool use on body or space representations are relatively well established in cognitive neuroscience. Several studies have shown, for example, that active tool use results in a facilitated integration of multisensory information in peripersonal space, i.e. the space directly surrounding the body. However, it remains unknown to what extent similar mechanisms apply to the use of virtual-robotic tools, such as those used in the field of surgical robotics, in which a surgeon may use bimanual haptic interfaces to control a surgery robot at a remote location. This paper presents two experiments in which participants used a haptic handle, originally designed for a commercial surgery robot, to control a virtual tool. The integration of multisensory information related to the virtual-robotic tool was assessed by means of the crossmodal congruency task, in which subjects responded to tactile vibrations applied to their fingers while ignoring visual distractors superimposed on the tip of the virtual-robotic tool. Our results show that active virtual-robotic tool use changes the spatial modulation of the crossmodal congruency effects, comparable to changes in the representation of peripersonal space observed during real-world tool use. Moreover, when the virtual-robotic tools were held in a crossed position, the visual distractors interfered strongly with tactile stimuli that was connected with the hand via the tool, reflecting a remapping of peripersonal space. Such remapping was not only observed when the virtual-robotic tools were actively used (Experiment 1), but also when passively held the tools (Experiment 2). The present study extends earlier findings on the extension of peripersonal space from physical and pointing tools to virtual-robotic tools using techniques from haptics and virtual reality. We discuss our data with respect to learning and human factors in the field of surgical robotics and discuss the use of new technologies in the field of cognitive neuroscience.